(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The main aim of the present investigation is identification of bioactive compounds from methanolic extraction of Saussurea lappa clarke and Premna mucronata, by GC–MS analysis and also evaluated the phytochemical screening. Methanolic extraction of S. lappa clarke and P. mucronata revealed the presence of flavonoids, phenolic compounds, triterpenoids, tannins, saponins, amino acids, proteins, steroids, gums and carbohydrates. Gas chromatography-mass spectrometry (GC-MS) analysis of the methanol extracts of S. lappa clarke and P. mucronata was performed on a GC-MS equipment. In-vitro antioxidant activity (hydroxyl radaical scavenging activity, determination of reducing power, metal chelating activity, carbon tetrachloride (ccl4) induced lipid peroxidation, inhibitory test on protein oxidative modification, lipid peroxidation assay, catalase assay and reduced glutathione assay) was evaluated by adopting different methods. The GC-MS analysis has shown the presence of different bio active compounds in the methanolic extract of S. lappa clarke A total of 10 compounds were identified in that the main active compounds are 2-nonynoic acid, lupeol and dodecanal and P. mucronata GC-MS analysis showed the presence 15 bio active compounds in that the main compounds are L-cysteine, undecanoic acid, tetradecanoic acid, gamma.-sitosterol, vitamin E acetate and fucosterol. From the results, it is evident that S. lappa clarke and P. mucronata contains various phytocomponents and is recommended as a plant of phytopharmaceutical importance. Methanolic extraction of S. lappa clarke and P. mucronata possesses antioxidant activity.